Fast multistation water/fat imaging at 3T using DREAM-based RF shimming - Hooijmans, Melissa T.; Dzyubachyk, Oleh; Nehrke, Kay; Koken, Peter; Versluis, Maarten J.; Kan, Hermien E.; Börnert, Peter (Journal of magnetic resonance imaging, 2015)
Purpose To show the effect, efficiency, and image quality improvements achievable by Dual Refocusing Echo Acquisition Mode (DREAM)‐based B1+ shimming in whole‐body magnetic resonance imaging (MRI) at 3T using the example of water/fat imaging. Materials and Methods 3D multistation, dual‐echo mDixon gradient echo imaging was performed in 10 healthy subjects on a clinical 3T dual‐transmit MRI system using station‐to‐station adapted B1+ shimming based on fast DREAM B1+ mapping. Whole‐body data were obtained using conventional quadrature excitation and station‐by‐station adapted DREAM‐based B1+ shimmed excitation, along with the corresponding B1+ maps for both excitation modes to assess image quality and radiofrequency (RF) performance. Results Station‐dependent DREAM‐based B1+ shimming showed significantly improved image quality in the stations covering the upper legs, pelvis, and upper body region for all subjects (P < 0.02). This finding is supported by corresponding B1+ maps showing an improved B1+ homogeneity and a more precise flip angle in the DREAM‐based B1+ shimmed excitation (P < 0.01). Furthermore, the very short dual‐channel DREAM B1+ mapping times of less than 2 seconds facilitate quick B1+ shimming. Conclusion Station‐dependent DREAM‐based B1+ shimming improved RF performance and image quality and is therefore a promising technique for whole‐body multistation imaging applications. J. Magn. Reson. Imaging 2015;42:217–223. © 2014 Wiley Periodicals, Inc.